The identification and expression analysis of walnut Acyl-ACP thioesterases - Wang, Hui; Shi, Jianqing; Guo, Wanhui; Sun, Xiaohui; Niu, Shuhui; Chen, Li; Liu, Shenghong; Ma, Lei (Frontiers in Genetics, 2024)
Walnuts (Juglans regia L.), renowned for their nutritional potency, are a rich source of unsaturated fatty acids. Their regular intake plays a pivotal role in health maintenance and recuperation from a myriad of ailments. Fatty acyl-acyl carrier protein thioesterases, which orchestrate the hydrolysis of acyl-ACP thioester bonds, thereby yielding fatty acids of varying chain lengths, are instrumental in augmenting plant fatty acid content and modulating the balance between saturated and unsaturated fatty acids. Despite some investigative efforts into the synthesis and metabolic pathways of fatty acids in walnuts, our comprehension of Fat in walnuts remains rudimentary. This research undertook a comprehensive characterization of the JrFat family, predicated on the complete genome sequence of walnuts, leading to the identification of 8 JrFat genes and an exploration of their protein physicochemical properties. Utilizing Arabidopsis and soybean Fat genes as outgroups, JrFat genes can be categorized into 5 distinct subgroups, three of which encompass a pair of homologous gene pairs. These genes have demonstrated remarkable conservation throughout the evolutionary process, with highly analogous conserved base sequences. The promoter region of JrFats genes predominantly harbors light response and plant hormone response regulatory elements, with no discernible disparity in promoter elements among different JrFats. Predictive analyses indicate that JrFats proteins engage extensively with walnut fatty acid synthesis and metabolism-associated proteins.qRT-PCR analysis reveals an initial surge in the expression of JrFats during the development of walnut kernels, which either stabilizes or diminishes following the hard core period.Homologous gene pairs exhibit analogous expression patterns, and the expression trajectory of JrFats aligns with the dynamic accumulation of fatty acids in kernels. The expression of JrFatA2 exhibits a strong correlation with the content of Alpha-linolenic acid, while the expression of JrFatB2 is inversely correlated with the content of two saturated fatty acids. Collectively, these findings enrich our understanding of fatty acid synthesis and metabolism in walnuts and furnish gene resources for enhancing the content and ratio of fatty acids in walnuts.